Combination of Intensive Chemotherapy and Anticancer Vaccines in the Treatment of Human Malignancies: The Hematological Experience. (2nd June 2010) - Liseth, Knut; Ersvær, Elisabeth; Hervig, Tor; Bruserud, Øystein
Abstract : In vitro studies have demonstrated that cancer-specific T cell cytotoxicity can be induced both ex vivo and in vivo, but this therapeutic strategy should probably be used as an integrated part of a cancer treatment regimen. Initial chemotherapy should be administered to reduce the cancer cell burden and disease-induced immune defects. This could be followed by autologous stem cell transplantation that is a safe procedure including both high-dose disease-directed chemotherapy and the possibility for ex vivo enrichment of the immunocompetent graft cells. The most intensive conventional chemotherapy and stem cell transplantation are used especially in the treatment of aggressive hematologic malignancies; both strategies induce T cell defects that may last for several months but cancer-specific T cell reactivity is maintained after both procedures. Enhancement of anticancer T cell cytotoxicity is possible but posttransplant vaccination therapy should probably be combined with optimalisation of immunoregulatory networks. Such combinatory regimens should be suitable for patients with aggressive hematological malignancies and probably also for other cancer patients.